Social and Emotional Interaction of Autistic Children in SLB - Fitriyani, Akmal Satya Fazri, Dinda Nuria, Ella Sintya, (ALACRITY : Journal of Education, 2023)
Autism is a symptom that occurs in childhood, which describes loneliness, difficulty speaking, carrying out activities directly and exclusively, sportsmanship, and memorizing things without thinking. Autism is an abnormal change in the human nervous system, mainly caused by genetic factors. This research uses qualitative methodology and a case study strategy. The research subjects are autistic children at the Wijaya Kusumah State SLB in Bekasi, West Java. Research data was taken through observation, interviews and documentation. Based on the results of interviews and observations, the information received can be seen. Autism Teacher at SLB Wijaya Kusumah regarding the social and emotional interactions of children at SLB, that children with autism have difficulty speaking. When children with autism borrow things from their peers, they will immediately hit them and throw a tantrum if they don't give them because the child with autism has difficulty speaking and experiences disorders in the nervous brain system. Internal factors that cause barriers to socio-emotional interactions in autistic children are nerve damage and difficulty speaking. External factors that can influence barriers. Family factors, nutritional factors, culture, playmates and school friends play a role in the social-emotional interactions of autistic children. Poor nutritional factors can also cause disturbances in brain development, including the development of social interactions. A culture that does not support autistic children can also hinder the development of their social interactions.